Effect of Blue Light Blocking and Anti-Glare Glasses on Computer Vision Syndrome - Jahangir, Muhammad Mujtaba; Irshad, Dr. Asima; Shahzaib, Muhammad; Hassan, Faiza; Inam, Nageena (Medical Journal of South Punjab, 2014)
Objective: To compare the effect of blue light blocking filter and anti-glare coating on computer vision syndrome. Methodology: Randomized Control Trial was conducted Ayesha Saddiqua Trust Hospital from May 2023 to April 2024. This randomized controlled trial consisted of 36 participants, divided equally into Group A (blue blocking filter glasses) and Group B (anti-glare glasses). Participants were selected based on inclusion criteria such as having 8 hours of screen time per day, being computer users aged 18 to 40 years, and experiencing symptoms like headache, eye strain, and dry eyes. Data collection involved the Schirmer test and the OSDI questionnaire to assess dry eye disease severity. Participants diagnosed with dry eye were randomly assigned to use either anti-glare or blue-blocking glasses, with assessments conducted at multiple intervals over three months. Results: 36 participants aged between 20-40 years were included in study for the comparison of blue-blocking and anti-glare glasses, the baseline mean difference between groups was 0.402 (p=0.200), which was not statistically significant. However, after three months, the mean difference was 0.813 (p<0.05), indicating significant improvement. Regarding eye dryness, the baseline mean difference was 2.14 (p=0.441), which was not statistically significant, but after three months, the mean difference was 6.63 (p<0.05), showing significant improvement. Conclusion: Both blue blocking and anti-glare interventions significantly alleviated symptoms of blue blocking and eye dryness, with blue blocking filter glasses showing greater improvements than anti-glare glasses.